A method for switching the selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off to achieve sustainable water purification
By designing an electronically controlled two-site catalyst (Fe-in-NCNT) to switch selective Fenton-like reaction mode, the problem that existing water treatment technologies are difficult to remove low-concentration target organic pollutants is solved, and efficient removal of mixed pollutants and sustainable water treatment is achieved.
Patent Information
- Application Number
- CN202411802922.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing water treatment technologies are difficult to effectively remove low concentrations of target organic pollutants, especially in the case of coexistence of multiple pollutants, and the traditional methods are less selective and efficient.
An electrically controlled two-site catalyst (Fe-in-NCNT) is designed to achieve the separation and generation of FeIV=O and 1O2 through electrical on/off switching, and a series method combining interface reaction and aqueous phase reaction is used for sustainable water purification.
It realizes efficient removal of mixed pollutants of different reaction properties, simplifies operating procedures, reduces costs, and improves the sustainability and selectivity of water treatment.
Smart Images

Figure CN119285046B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water treatment, and in particular to a method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst through electrical on / off. Background Art
[0002] In recent years, emerging pollutants (ECs) that persist in aquatic environmental resources have attracted worldwide attention due to their potential risks to human health and ecosystems. However, in practical situations, conventional water treatment technologies are rarely able to continuously remove target pollutants, especially at low concentrations. Therefore, selective removal of target organic pollutants from contaminated water is expected to enhance the sustainability of environmental management. Non-radicals in advanced oxidation processes are excellent choices for selective removal of target organic pollutants due to their low sensitivity to non-target substrates, high electrophilicity, and specific affinity for electron-rich pollutants.
[0003] The Fenton-like reaction mediated by peroxymonosulfate (PMS) activation is one of the most promising technologies for selectively generating desired reactive oxygen species (ROS). The non-radical reactive species can be divided into singlet oxygen ( 1 O2), direct electron transfer and high-valent metal oxygen complexes (Fe IV =O). In particular, the surface-bound Fe IV =O shows higher local reactivity towards pollutants adsorbed on the catalyst surface, while free 1 O2 rapidly oxidizes the target pollutants in the solution with its high reactivity and mobility. Considering that actual wastewater contains a variety of ECs with different properties (some tend to adsorb on the catalyst surface, while others are not easily adsorbed), regulating the reaction between the interface and the aqueous phase is the key to effectively achieve targeted removal of specific pollutants. Therefore, the tandem method combining interfacial reaction and aqueous phase reaction is an effective means to completely degrade a variety of target organic matter in water.
[0004] The selective generation of the desired ROS during PMS activation is a complex challenge. The selective adsorption of different O atoms on PMS (O III -S=(O)2-O II -O I -H) and the direction of electron transfer between the active site and PMS will affect the activation pathway of PMS. IV =O is through heterolytic fission III -S bond is generated, accompanied by directional electron transfer from the Fe site to the PMS, while the free 1 The generation of O2 mainly depends on the electron donation rate of PMS and the OI Unfortunately, most current studies focus on the generation of a single free or bound ROS based on one catalyst, which makes the combined technology (a tandem process of interfacial reaction and aqueous phase reaction) lengthy and expensive, involving at least two separate units. Another limitation is that during the PMS activation process, Fe IV =O and 1 The production of O2 is very low. Therefore, a dual-site catalyst was fabricated in one device to effectively and selectively convert Fe IV =O and 1 O2 separation generation is a very promising and challenging task, which will greatly simplify the expected tandem process. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for achieving sustainable water purification by switching the selective Fenton-like reaction mode on a dual-site catalyst through electric on / off. The present invention first designs a unique graphite carbon semi-coated Fe3C@Fe 0 The nanoparticles are encapsulated in nitrogen-doped carbon nanotubes (NCNT) and are electrically controlled dual-site catalysts (Fe-in-NCNT). The PMS activation pathway is changed by a simple electrical switch (on / off), thereby achieving the separation and efficient selective generation of Fe. IV =O or 1 O2. In one operating unit, it is proposed to combine Fe IV =O and free 1 O2 cascade process for sustainable purification of water bodies with mixed pollutants of different reactive properties.
[0006] The object of the present invention is to provide a method for switching a selective Fenton-like reaction mode on a dual-site catalyst by electric on / off to achieve sustainable water purification, comprising the following steps: placing water resources containing organic pollutants in an electrolytic cell, using a Fe-in-NCNT electrode as a cathode and a platinum sheet as an anode to construct an electrolytic device, and intermittently energizing the electrolytic device;
[0007] The Fe-in-NCNT electrode is based on carbon paper, and the surface of the base electrode is coated with Fe-in-NCNT material. The Fe-in-NCNT material is graphite carbon semi-coated Fe3C@Fe 0 The nanoparticles include iron nanoparticles and nitrogen-doped carbon nanotubes. The nitrogen-doped carbon nanotubes contain Fe3C-coated zero-valent iron nanoparticles inside, and one end of the iron nanoparticle is coated with multiple layers of graphite (i.e., half-coated).
[0008] The iron nanoparticles of the present invention are located inside the nitrogen-doped carbon nanotubes, and the N element can promote the growth of the compartment structure, so that the iron nanoparticles fall into the compartment to form a structure in which one end of the nanoparticle is half-covered by a graphite layer, so that the material can affect the electron density of carbon atoms under the action of an electric field, thereby causing a change in active species.
[0009] In some embodiments of the present invention, the organic pollutants include one or more of bisphenol A (BPA), ciprofloxacin (CIP), methyl paraben (MeP), p-cresol (MP), 4-chlorophenol (4CP) and phenol (PE), 4-acetaminophen (AcP), sulfachloropyrazine (SCP) and sulfamethoxazole (SMX).
[0010] In some embodiments of the present invention, the Fe-in-NCNT electrode is prepared by the following method:
[0011] Melamine is mixed with an iron source and calcined under an inert atmosphere to obtain a Fe-in-NCNT substrate material;
[0012] The Fe-in-NCNT substrate material is dispersed in an organic solvent and then deposited on carbon paper to obtain the Fe-in-NCNT electrode.
[0013] In some embodiments of the present invention, the iron source is selected from ferric chloride hexahydrate.
[0014] In some embodiments of the present invention, the mass ratio of melamine to iron source is (12-6.5): (7-3.5), and further, the mass ratio is (12.4-6.2): (6.7575-3.378).
[0015] In some embodiments of the present invention, the calcination temperature is not less than 700° C., the calcination time is 3-5 h, and the heating rate is 5-10° C. / min.
[0016] In some embodiments of the present invention, the gas of the inert atmosphere includes argon and / or nitrogen; the flow rate of the gas in the inert atmosphere is 40-100 mL / min.
[0017] In some embodiments of the present invention, the concentration of the organic pollutants is 1-10 ppm.
[0018] In some embodiments of the present invention, (i) for organic pollutants with an adsorption amount of less than 15% and present in the solution, the free 1 O2 water phase reaction mode; for organic pollutants that are difficult to adsorb on the surface of the material, the electrical degradation mode can be used for 30-60 minutes.
[0019] (ii) For organic pollutants with an adsorption amount in the range of 15-25%, the reaction mode is selected as the aqueous phase reaction mode and the interface reaction mode; for multi-pollutant systems, the power is turned off for 30 minutes to remove most of the pollutants that are easily adsorbed on the material surface, and then the power is turned on for 90 minutes to completely remove other pollutants;
[0020] (iii) For organic pollutants with an adsorption amount >25%, the interface reaction mode is used. For those that are easily adsorbed on the material surface, the non-powered degradation mode can be used for 30-60 min.
[0021] Furthermore, intermittent power treatment can be understood as follows: (i) For pollutants with low adsorption capacity (<15%, region I) and pollutants present in solution, it is preferred to preferentially use the free adsorption capacity based on the formation of the adsorption capacity under the applied electric field. 1 (ii) For pollutants with moderate adsorption (15-25%, region II), the choice of reaction mode should take into account other factors such as operating costs, because the application of an electric field cannot significantly improve the removal rate, and the electrochemical reaction itself will generate additional energy consumption; (iii) For pollutants with large adsorption (>25%, region III), the interface reaction mode can be directly adopted, with Fe IV =O is the main active substance, and the adsorbed pollutants can be effectively degraded without additional energy input. The present invention uses materials to activate peroxymonosulfonate to generate free radicals to degrade pollutants, but the active species generated are different under the action of an electric field or not.
[0022] In some embodiments of the present invention, the electrolyte is potassium permonosulfonate (PMS), and the pH value of the electrolyte solution is 3-5;
[0023] A two-electrode DC power supply was used with a constant current of 10-40 mA.
[0024] The above technical solution of the present invention has the following advantages compared with the prior art:
[0025] 1. The present invention prepares Fe-based carbon nanotube cathode electrode (Fe-in-NCNT) by a one-step calcination method, which has a unique graphite carbon semi-coated Fe3C@Fe 0 The nanoparticles are encapsulated in a nitrogen-doped carbon nanotube (NCNT) structure, providing dual reaction sites for Fenton-like activation. When no electric field is applied, Fe-in-NCNT can activate PMS to produce high-valent iron (Fe IV =O); after applying the electric field, the active site changes from Fe to C, making the active species change from Fe IV =O is converted to singlet oxygen ( 1O2), which can effectively remove low ionization potential pollutants that are difficult to accumulate on the catalyst surface.
[0026] 2. The present invention studies the adsorption and degradation of low ionization potential electron-rich pollutants on catalysts, and can classify low ionization potential electron-rich pollutants with different adsorption characteristics into three removal modes: (i) For pollutants with low adsorption capacity (<15%), which mainly exist in the solution, the free electron-rich pollutants formed by the external electric field are preferentially used. 1 (ii) For pollutants with moderate adsorption (15-25%), the choice of reaction mode should take into account other factors such as operating costs, because the water phase reaction mode initiated by the electric field cannot significantly improve the removal rate, and the application of electricity itself will generate additional energy consumption; (iii) For pollutants with large adsorption (>25%), the interface reaction mode (i.e., power-off treatment) can be directly adopted to remove Fe IV =O is the main active substance, which can effectively degrade the adsorbed pollutants without additional energy input.
[0027] 3. Compared with the traditional series method, such as two units with two catalysts, the Fe-in-NCNT electrode material of the present invention can realize the switching of the selective Fenton-like reaction mode on the dual-site catalyst by electric on / off, thereby realizing sustainable water purification, avoiding the disadvantages of lengthy operation, high research cost, long cycle, etc., and has the advantage of simple operation.
[0028] 4. The Fe-in-NCNT electrode material prepared by the present invention has good PMS catalytic activity and achieves high selectivity and high yield of Fe IV =O (selectivity 95.0%, 30 min Fe IV =O cumulative concentration is 16605 μM) and 1 O2 (selectivity 90.5%, 30 min 1 The O2 cumulative concentration is 7674 μM), achieving sustainable and selective removal of target pollutants in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0030] Figure 1 TEM image of Fe-in-NCNT obtained in Example 1 of the present invention;
[0031] Figure 2 TEM image of Fe-out-NCNT obtained in Example 1 of the present invention;
[0032] Figure 3 The EPR spectra of the Fe-in-NCNT / PMS and Fe-in-NCNT / PMS+E systems obtained in Example 1 of the present invention;
[0033] Figure 4 The removal rates of nine different low ionization potential electron-rich pollutants by the Fe-in-NCNT / PMS and Fe-in-NCNT / PMS+E systems in Application Example 1 of the present invention;
[0034] Figure 5 It is the removal rate of SMX and BPA mixed pollutant system by Fe-in-NCNT / PMS and Fe-in-NCNT / PMS+E systems in series. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0036] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0037] Example 1
[0038] The specific preparation methods of the "Fe-in-NCNT" and "Fe-out-NCNT" carbon-based electrodes in this embodiment are as follows:
[0039] (1) Construction of Fe-in-NCNT material: Melamine and ferric chloride hexahydrate were uniformly mixed in a molar ratio of 4:1. The uniformly mixed powder was calcined in a tube furnace at 700°C for 3 h with a heating rate of 5°C / min. The gas atmosphere was argon (Ar) and the gas flow rate was 40 mL / min to obtain a fluffy black solid. The solid was ground into powder and immersed in 6 mol / L hydrochloric acid (HCl) with a volume 10 times the mass of the powder at room temperature for 36 h to remove unstable iron species to obtain a Fe-in-NCNT substrate material. The solid was then washed with water and ethanol three times and dried in an oven at 60°C for 12 h. 20 mg of the Fe-in-NCNT substrate material was weighed and ultrasonically dispersed in a mixed solution of ethanol and naphthol. The solid was then sprayed onto carbon paper using an ultrasonic sprayer to obtain a Fe-in-NCNT electrode.
[0040] (2) Construction of Fe-out-NCNT material: The Fe-in-NCNT obtained in step (1) was treated with aqua regia at 60°C for 24 h to remove the iron nanoparticles inside the Fe-in-NCNT, and then boiled at 100°C to remove the residual acid until it was completely evaporated. The NCNT prepared above with the Fe nanoparticles removed was washed with deionized water and then dried at 60°C for 12 h to obtain NCNT. Finally, the obtained NCNT was mixed with iron (III) chloride hexahydrate to obtain a uniform powder to ensure that its Fe content was the same as that in the Fe-in-NCNT, and then calcined in a tube furnace at 850°C for 3 h to obtain a Fe-out-NCNT substrate material, wherein the heating rate of the heating calcination was 5°C / min, the gas atmosphere was Ar, and the gas flow rate was 40 mL / min. The prepared Fe-out-NCNT was washed with deionized water and ethanol three times, and then dried at 60°C for 12 h. 20 mg of Fe-out-NCNT substrate material was weighed, ultrasonically dispersed in a mixed solution of ethanol and naphthol, and then sprayed onto carbon paper using an ultrasonic sprayer to obtain a Fe-out-NCNT electrode.
[0041] Characterization and performance testing:
[0042] 1. Characterization: The surface morphology and structure of the Fe-in-NCNT electrode and the Fe-out-NCNT electrode obtained in Example 1 were characterized by transmission electron microscopy (TEM). Figure 1 As shown in the figure, Fe nanoparticles can be observed in the nitrogen-doped carbon nanotubes, and there is a carbon layer at the bottom covering the Fe nanoparticles, which proves that the present invention successfully synthesized Fe3C@Fe with unique graphite carbon semi-coated 0 Nanoparticles are encapsulated in the structure of nitrogen-doped carbon nanotubes (NCNT), and Fe-in-NCNT electrode materials are obtained on the surface. Figure 2 As shown, there are Fe nanoparticles outside the nitrogen-doped carbon nanotubes (marked with red circles), indicating that the Fe-out-NCNT electrode material was successfully synthesized.
[0043] 2. Performance Test
[0044] The Fe-in-NCNT electrode and the Fe-out-NCNT electrode in Example 1 were used as electrochemical cathodes, and the sulfate radical (SO4 •- ) and hydroxyl radicals (HO • )、Singlet oxygen( 1 O2) and high-valent iron (Fe IV =O) for detection. -15,5-Dimethyl-1-pyrroline-N-oxide (DMPO) was used as a scavenger to react with SO4 •- , HO • and Fe IV =O forms a complex DMPO-SO4 •- 、DMPO-HO • The EPR resonance frequency was set at 9.85 GHz, and the ROS generated by activating 10 mM potassium peroxymonosulfonate (PMS) using Fe-in-NCNT and Fe-out-NCNT as cathodes were detected by electron paramagnetic resonance spectrometer (EPR). Figure 3 As shown. Using DMPO as a capture agent, it was detected that both the Fe-out-NCNT / PMS (no power supply) and Fe-out-NCNT / PMS+E (power supply) systems can produce SO4 •- and HO • , while the Fe-in-NCNT / PMS system produces Fe IV =O, Fe-in-NCNT / PMS+E system Fe IV =O signal disappears; 2,2,6,6-tetramethyl-4-piperidone hydrochloride (TEMP) is further used as a capture agent to detect the generated 1 O2, Fe-out-NCNT / PMS (no power supply) and Fe-out-NCNT / PMS+E (power supply) systems only produce trace amounts of 1 O2, the application of electric field 1 O2 signal intensity has no significant effect; while the Fe-in-NCNT / PMS system produces 1 The O2 intensity is about twice that of the Fe-out-NCNT / PMS and Fe-out-NCNT / PMS+E systems. Once the electric field is applied, the Fe-in-NCNT / PMS system 1 The O2 intensity increases rapidly, which is 4 times that of the Fe-in-NCNT / PMS system. This shows that Fe-in-NCNT can regulate its activation pathway through the electric field during the activation of PMS and selectively generate different ROS, while Fe-out-NCNT does not have such a feature, which is mainly attributed to the unique structural design of Fe-in-NCNT.
[0045] Application Example 1
[0046] The Fe-in-NCNT electrode obtained in Example 1 was applied as a catalytic material to a pollutant degradation reaction system to evaluate the ability of the catalytic material to degrade different types of electron-rich pollutants with low ionization potential. It was used as the cathode in the electrocatalytic reaction system, where the anode was a platinum sheet electrode with an electrode area of 5 cm 2. A two-electrode potentiostat was used as a DC power supply, and a constant current of 20 mA was applied. The pollutants (50 mL, 10 ppm) were degraded in a 10 mM PMS solution as a supporting electrolyte. The degradation time was 30 min, the reaction temperature was 20-25 °C, and the pH range was 3. The DC power supply must be removed for the performance evaluation of the non-electrochemical system. The other conditions were the same. The experimental results are shown in Figure 4 .
[0047] Depend on Figure 4 It can be seen that in region I, the degradation rates of bisphenol A (BPA), ciprofloxacin (CIP) and methyl paraben (MeP) in the Fe-in-NCNT / PMS system are relatively low, which may be due to the low adsorption amount (3.19-3.77 mg / g) and difficulty in adsorbing Fe. IV =O contact. When an electric field is applied, the main active species consists of surface-bound Fe IV =O is converted to free 1 O2 resulted in a significant increase in the removal of BPA, CIP, and MeP (34-39%), which is due to the 1 The result is that the O2 contact opportunity increases. In region II, after switching to the Fe-in-NCNT / PMS+E system, the degradation rates of p-cresol (MP), 4-chlorophenol (4CP) and phenol (PE) increased slightly (12-17%). In region III, 4-acetaminophen (AcP), sulfachloropyrazine (SCP) and sulfamethoxazole (SMX) had higher adsorption capacities (5.28 ~ 8.57 mg / g), and Fe IV =O and 1 O2 had no significant effect on its degradation rate.
[0048] Example 2
[0049] Based on the results of Application Example 1, the present invention proposes the following selection interface ROS (Fe IV =O) or aqueous ROS ( 1 Guidelines for selective removal of target pollutants by O2: (i) For pollutants with low adsorption capacity (<15%, region I) and pollutants present in solution, it is recommended to preferentially remove the free O2 by the formation of an external electric field. 1 (ii) For pollutants with moderate adsorption (15-25%, region II), the choice of reaction mode should take into account other factors such as operating costs, because the application of an electric field cannot significantly improve the removal rate, and the electrochemical reaction itself will generate additional energy consumption; (iii) For pollutants with large adsorption (>25%, region III), the interface reaction mode can be directly adopted, with Fe IV=O is the main active substance, which can effectively degrade the adsorbed pollutants without additional energy input. Considering the diversity of pollutants in actual water bodies, the present invention proposes a series mode of interfacial reaction and water phase reaction, and tests are carried out. The experimental results are as follows Figure 5 As shown in the mixed pollutant system of SMX and BPA, the interface reaction model (Fe IV =O, i.e., power-off treatment), 86.1% of SMX was effectively removed within 30 min, while only 20.5% of BPA was removed, which is consistent with the above-mentioned pollutant removal guidelines. As expected, the degradation efficiency of BPA was significantly improved after the application of the electric field, and the degradation efficiency of BPA was significantly improved by Fe IV =O and 1 The O2 cascade reaction lasted for 120 min, effectively achieving the complete removal of BPA and SMX from the mixed pollutants.
[0050] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off, characterized in that: The following steps are involved: The water resource containing organic pollutants is placed in an electrolytic cell, an Fe-in-NCNT electrode is used as a cathode, a platinum sheet is used as an anode, an electrolytic device is constructed, and the electrolytic device is intermittently energized for treatment; The Fe-in-NCNT electrode is based on carbon paper, and the surface of the base electrode is coated with Fe-in-NCNT material, and the Fe-in-NCNT material includes iron nanoparticles and nitrogen-doped carbon nanotubes, and the nitrogen-doped carbon nanotubes contain Fe3C-coated zero-valent iron nanoparticles inside, and one end of the iron nanoparticle is coated with multiple layers of graphite; The intermittent power-on process: (i) For organic pollutants with an adsorption amount of less than 15% and present in solution, the free 1 The water phase reaction mode of O2; (ii) For organic pollutants with an adsorption amount in the range of 15-25%, the reaction mode selected is the water phase reaction mode and the interface reaction mode; (iii) For organic pollutants with adsorption amounts > 25%, the interface reaction mode was adopted.
2. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off according to claim 1, characterized in that: The organic pollutants include one or more of bisphenol A, ciprofloxacin, methyl parahydroxybenzoate, p-cresol, 4-chlorophenol and phenol, 4-acetaminophen, sulfachloropyrazine and sulfamethoxazole.
3. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off according to claim 1, characterized in that: The Fe-in-NCNT electrode is prepared by the following method: Melamine is mixed with an iron source and calcined under an inert atmosphere to obtain a Fe-in-NCNT substrate material; The Fe-in-NCNT substrate material is dispersed in an organic solvent and then deposited on carbon paper to obtain the Fe-in-NCNT electrode.
4. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off according to claim 3, characterized in that: The iron source is selected from ferric chloride hexahydrate.
5. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off according to claim 3, characterized in that: The mass ratio of melamine to iron source is (12-6.5): (7-3.5).
6. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off according to claim 3, characterized in that: The calcination temperature is not less than 700°C, the calcination time is 3-5 h, and the heating rate is 5-10°C / min.
7. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off according to claim 3, characterized in that: The gas of the inert atmosphere includes argon and / or nitrogen; the flow rate of the gas in the inert atmosphere is 40-100 mL / min.
8. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off according to claim 1, characterized in that: The concentration of the organic pollutants is 1-10 ppm.
9. A method for achieving sustainable water purification by switching a selective Fenton-like reaction mode on a dual-site catalyst by electrical on / off according to claim 1, characterized in that: The electrolyte used is potassium peroxymonosulfonate, and the pH value of the electrolyte solution is 3-5; A two-electrode DC power supply is used with a constant current of 10-40mA.
Citation Information
Patent Citations
Preparation method and application of loofah sponge biomorphic supported nitrogen-doped carbon nanotube coated iron nanoparticle Fenton-like catalyst
CN112121843A
Carbon nanotube and graphite flake hybrid material and preparation method and application thereof
CN112264000A